N‐glycosylation of PD‐1 promotes binding of camrelizumab. (15th October 2020) - Liu, Kefang; Tan, Shuguang; Jin, Wanjun; Guan, Jiawei; Wang, Qingling; Sun, Huan; Qi, Jianxun; Yan, Jinghua; Chai, Yan; Wang, Zhongfu; Deng, Chuxia; Gao, George F
Abstract: PD‐1 is a highly glycosylated inhibitory receptor expressed mainly on T cells. Targeting of PD‐1 with monoclonal antibodies (MAbs) to block the interaction with its ligand PD‐L1 has been successful for the treatment of multiple tumors. However, polymorphisms at N‐glycosylation sites of PD‐1 exist in the human population that might affect antibody binding, and dysregulated glycosylation has been observed in the tumor microenvironment. Here, we demonstrate varied N‐glycan composition in PD‐1, and show that the binding affinity of camrelizumab, a recently approved PD‐1‐specific MAb, to non‐glycosylated PD‐1 proteins from E. coli is substantially decreased compared with glycosylated PD‐1. The structure of the camrelizumab/PD‐1 complex reveals that camrelizumab mainly utilizes its heavy chain to bind to PD‐1, while the light chain sterically inhibits the binding of PD‐L1 to PD‐1. Glycosylation of asparagine 58 (N58) promotes the interaction with camrelizumab, while the efficiency of camrelizumab to inhibit the binding of PD‐L1 is substantially reduced for glycosylation‐deficient PD‐1. These results increase our understanding of how glycosylation affects the activity of PD‐1‐specific MAbs during immune checkpoint therapy. Synopsis: PD‐1 is a highly glycosylated receptor with a varied N‐glycan composition. The therapeutic antibody camrelizumab binds to the N58 glycan of PD‐1 and absent glycosylation results in decreased binding affinity and PD‐1/PD‐L1 blocking efficiency. PD‐1 shows a varied N‐glycan composition and glycosylation of PD‐1 is critical for PD‐1 stability. N58 glycosylation of PD‐1 promotes the interaction and contributes to the high binding affinity of camrelizumab. The efficiency of camrelizumab to inhibit the binding of PD‐L1 to N58 glycosylation‐deficient PD‐1 is substantially reduced. Abstract : PD‐1 is a highly glycosylated receptor with a varied N‐glycan composition. The therapeutic antibody camrelizumab binds to the N58 glycan of PD‐1 and absent glycosylation results in decreased binding affinity and PD‐1/PD‐L1 blocking efficiency.